IMPLIKASI AGAMA DALAM PILKADA DKI JAKARTA 2017 (TELAAH ATAS SIYASAH SYAR’IYYAH) - Nurchaliq Majid (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The main problem of this research is how is the Religious Implication of 2017 DKI Jakarta Election (Review of Siyasah Syar'iyah)? The subject matter is divided into three sub-problems, namely: 1) Is choosing a community leader based on religion a form of actualization of religious freedom? 2) What are the perceptions of the DKI Jakarta community in choosing community leaders? The type of research used is qualitative research with a normative approach and also socio-legal research with an empirical descriptive approach. Methods of general data collection, interviews and documentation, processing techniques and data analysis carried out through three stages, namely Data Reduction, Presentation and Conclusion. The results of this study indicate that: 1) choosing public leaders based on religion is a form of actualization of religious freedom. The form of worship that is actualized in choosing leaders is the right of every citizen promoted by the constitution. Actualization and explosion of choosing community leaders based on religion or Islamic leadership dogma cannot be intervened and is limited. 2) Perception of the people of DKI Jakarta about choosing community leaders after religion cannot be separated from the pros and cons. The existence of primordial (religious) sentiments certainly has an influence in the political contestation of the DKI Jakarta Election. Not to mention people who like and cannot choose non-Muslim leaders. But apart from that, people's hopes for DKI Jakarta continue to be echoed. 3) Religious attitudes in the DKI Jakarta Regional Election in the Syari'ah Siyasah Perspective relating to aspects of morality as an embodiment of Islamic values. The foundation for choosing leaders is not only in the name of ordinary religion, but religious values can also be discussed. Like honesty, justice, benefit, equality, and prosperity. The implications of this study are 1) choosing based on religion is no longer reviewed as a form of intolerance. Because basically choosing (choosing, expanding choices) is part of the form of worship promoted by the constitution. 2) This research aims to open insight into the importance of understanding the essence of leadership in Islam. Either from the revision of the verse book or Siyasah Syariyyah. 3) Regarding how the Sharia Siyasah Perspective in choosing public leaders is religious, then of course people must understand in choosing aspects to prioritize aspects of morality, these leaders must be fair and trustworthy towards the people they lead.